PERDAGANGAN MANUSIA / HUMAN TRAFFICKING (SUATU PENDEKATAN POSKOLONIAL GAYATRI C. SPIVAK) - Humen, Alfridus; Saunoah, Leonardus; Yanti Bikefi, Maria; Naisuan, Yovanti; Binsasi, Nofrianus; Grasela Bukifan, Maria; Marice Pedja, Angela; Kristiani Seran, Maria; Melania Nahak, Fatria (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
Many people think that human trafficking is the act of selling people (humans) to other people. However, this definition is not limited to “sales” alone. Then, it is important to know that in law, human trafficking is known as human trafficking. trafficking in persons or human trafficking is the act of recruiting, transporting, harboring, sending, transferring or receiving a person with the threat of violence, use of force, kidnapping, confinement, forgery, fraud, abuse of power or a vulnerable position, debt bondage or providing payments or benefits, so that obtain the consent of the person who has control over another person, whether carried out within a country or between countries, for the purpose of exploiting or causing the person to be exploited. The purpose of this research is to find out the meaning of Human Trafficking, the factors that cause Human Trafficking, and what approaches are used in Human Trafficking. The method used is a qualitative approach. Based on the discussion that has been used, the conclusion is that Human trafficking is a crime that involves coercion or pressure on someone to provide labor or services, or engage in commercial sex acts, so that many people think that human trafficking is an act of selling people or humans to others. By studying human trafficking, we can contribute significantly to reducing this crime, protecting victims, and creating a safer world.